Biopolítica e formação: vida, exceção e profanação na educação - Azevedo, Mauricio Cristiano de (2017)
This bibliographical analysis presents the debate on biopolitics, in its current stage, and its implications, in educational terms, considering, in particular, the idea of formation. The work is grounded, therefore, in the discussions of the philosophy of education and aims to indirectly echo its results in the research area of teacher training. It is centrally concerned with interpreting the claim of the philosopher Giorgio Agamben that, at present, the camp, and no longer the city, constitutes the political paradigm par excellence. To do so, the analysis sets out a panorama of the conceptual debate around the notion of biopolitics, exposing it through the reconstruction of arguments of Michel Foucault, Roberto Esposito, Antonio Negri and Michael Hardt. Then, the work reconstructs core points of Agamben's thought, the central author in the present study, and analyzes the concepts of life, exception, and profanity. It also turns to the problem of the legal-political status of the concentration camps and to the way in which, at the present moment of capitalist development, this status establishes itself within the social life and thus leads to a crisis of the traditional notion of subject. The notions of subject and experience, as thoughts in the theoretical framework of modern philosophies, are rescued. The work also updates the discussions in contemporary terms, now oriented by the linguistic model. In the end, the argumentative course focuses on the thinking path of education, rescuing its ontological condition and opening space for a counter economic and profane strategy analysis to permeate the educational devices in operation. It proposes, then, to think a broad idea of formation as desecration of the school economy, animated by what it calls "pedagogical machine". As it does not pursue systemic answers to the problems identified, this work does not endorses the idea of a conversion of the educational system; however, it suggests that the educational system, guided by state projects and world contingencies, is permeated with ideas and practices of a broader formation rather than with short-term objectives of the schooling process. Such an idea of broad formation, as a possibility to be developed, is a tributary of the human formation models represented by the ancient paideia, by the modern bildung and by the contemporary omnilateral formation. In this idea, there is a possibility of an extension of the battlefield of the biopolitics by the being. A pretense of biopower is, alongside a life of its form, to produce bare life, mere survival. In these terms, an education that is not reducible to the condition of social technology to produce docile subjects that can be useful and functional to the interests and demands of power, is conceived as the one in which there is always a possibility of the constitution of life forms by which biopower does not allow the disconnection between life and form. A form-of-life (the strongest sense of the concept, according to which a life can never be broken off from its form) is, above all, thought. Even the habitual ways of life or the materiality of corporeal processes, when they not allow a split into its form and bare life, they are consolidated form-of-life, and as such exhibit thought in its most human sense: that of the most personal and free decision for a life of its own. This is a power of life to be safeguarded, in the terms proposed by this work, by the idea of defiling formation. The methodological guidelines adopted in the study are from reconstructive hermeneutics with elements of the paradigmatic method.